Mechanical and Thermal Characteristics of Hybrid Composites Fortified with Flax, Banyan, and Glass Fibers for Automobile Safety Applications - S. Baladivakar; M.S. Starvin; J. Bensam Raj (Journal of Natural Fibers, 2022)
Automobile sector is growing day by day due to the globalization and the urbanization. Further, the luxury life of human beings leads to the new development in the production of automobiles. Consumers are looking for fuel economy with safety features in automobiles. Hence, the weight reduction and strength performance of components play major role in manufacturing of automobiles. In this current investigation, we tried to develop new composite materials with light weight and better thermal and mechanical characteristics using natural and synthetic fibers. Totally, six types of composites were manufactured, namely, Epoxy/Banyan, Epoxy/Glass, Epoxy/Flax, Epoxy/Banyan/Flax, Epoxy/Banyan/Glass, and Epoxy/Flax/Glass by conventional hand layup method by keeping matrix-to-fiber ratio as 60:40. Mechanical and thermal characteristics of the composites were examined. Based on the thermal behavior of composites, Epoxy/Banyan composite was selected as the suitable candidate for thermal insulation applications in automobile industries as exhibited least thermal conductivity of 0.112 W/mK. Further, the mechanical characteristics were tested for Epoxy/Banyan composite. Results displayed the properties as: tensile strength − 75 MPa; flexural strength − 113 MPa; impact strength − 12.8 kJ/m2.